Controlling the Facet of ZnO during Wet Chemical Etching Its (0001¯) O‐Terminated Surface. Issue 14 (28th February 2020) - Sun, Mei; Yu, Bocheng; Hong, Mengyu; Li, Zhiwei; Lyu, Fengjiao; Li, Xing; Li, Zhihong; Wei, Xianlong; Zhang, Zheng; Zhang, Yue; Chen, Qing
Abstract: Special surface plays a crucial role in nature as well as in industry. Here, the surface morphology evolution of ZnO during wet etching is studied by in situ liquid cell transmission electron microscopy and ex situ wet chemical etching. Many hillocks are observed on the (000 1 ¯ ) O‐terminated surface of ZnO nano/micro belts during in situ etching. Nanoparticles on the apex of the hillocks are observed to be essential for the formation of the hillocks, providing direct experimental evidence of the micromasking mechanism. The surfaces of the hillocks are identified to be 01 1 ¯ 3 ¯ crystal facets, which is different from the known fact that 01 1 ¯ 1 ¯ crystal facets appear on the (000 1 ¯ ) O‐terminated surface of ZnO after wet chemical etching. O2 plasma treatment is found to be the key factor for the appearance of 01 1 ¯ 3 ¯ instead of 01 1 ¯ 1 ¯ crystal facets after etching for both ZnO nano/micro belts and bulk materials. The synergistic effect of acidic etching and O‐rich surface caused by O2 plasma treatment is proposed to be the cause of the appearance of 01 1 ¯ 3 ¯ crystal facets. This method can be extended to control the surface morphology of other materials during wet chemical etching. Abstract : High‐index 01 1 ¯ 3 ¯ facets instead of low‐index 01 1 ¯ 1 ¯ facets of ZnO are controllably obtained through O2 plasma treatment before in situ or ex situ chemical etching the (000 1 ¯ ) O‐terminated surface of ZnO. Direct experimental evidence of the micromasking mechanism for the hillocks formation is also provided by in situ LCTEM study.